A new approach for in situ analysis in fully coupled earth system models - Turuncoglu, Ufuk Utku; Önol, Baris; Ilicak, Mehmet (ACM, 2019)
This work focuses on enabling the use of existing in situ analysis and visualization methods within the model coupling framework, which is specially designed software layer to combine physical components of Earth system (i.e., atmosphere, ocean) through a standardized calling interface to simplify common tasks such as interpolation among different numerical grids and synchronization of the model components. The new approach enables simultaneous analysis of the vast amount of data produced by a multi-component Earth system model in an integrated way and facilitates efficient, interoperable, and optimized data analysis and visualization workflows for Earth system science applications. To demonstrate the flexibility and the capability of the new approach, a fully coupled regional atmosphere-ocean modeling application that aims to investigate air-sea interaction in a very high spatial and temporal resolution has been implemented. In the use case application, both the simulation and in situ visualization application run in parallel on a large-scale HPC platform with both software and hardware rendering support through the use of accelerators.